The Cybernetic Writing Pad: Information Technology and the Retheorization of the Chinese Script, 1977-1986. Issue 3 (3rd July 2021) - Hou, Jue
Abstract: This study examines the script crisis that emerged in China during the late 1970s and early 1980s, when the old ideology of state phonocentrism and the new wave of computer science demanded the abandoning of Chinese characters altogether. Under the project of establishing new human-machine interfaces, national debates over such technical issues as the statistical properties of Chinese according to Claude Shannon's information theory took place in various venues, challenging the conventional language ideologies. As linguists and engineers rallied to collaborate on the scriptal modernization project on the basis of the discursive space opened up by critiques of the 1977 Simplification Scheme, efforts to integrate Chinese script into computer data-storage formats ended up destabilizing the understanding of Chinese writing that conventionally takes " zi " as opposed to " ci " as its basic unit. The shifting foci of script reform discourses during the period demonstrate that the rise of information technology and resumed debates over script reform jointly instigated a retheorization of written Chinese.